Valorisation des aménités et développement territorial : le rôle des Parcs Naturels Régionaux - Jean-Christophe Dissart; Amédée Mollard; Dominique Vollet (VertigO)
Two complementary approaches were used to show the potential links between environmental amenities, territorial rent and the development process. The first approach is experimental and multidisciplinary and associates the fields of ecology, cognitive science, management and economics, in order to assess the quality in terms of amenities of visited areas (supply) and their perception (demand), then their potential in terms of territorial rent in the Massifs of Bauges and Sancy (France). The second approach uses quantitative methods with a control group. It compares indicators of socioeconomic development, spatial structure and amenity endowment of municipalities that are members of RNPs in Auvergne and Rhône-Alpes, matched to similar municipalities located outside RNPs. The first approach identified six amenity systems perceived positively by “users” and significantly differentiated according to visit mode (permanent or temporary). However, their environmental preferences result in limited territorial rents in the study areas, whether for products or services. Nonetheless a significant rent potential has been highlighted for selected products. The second approach showed that RNP member municipalities exhibit higher tourism indicator values (accommodation density, employment) and that their economy is not adversely affected by RNP membership. Therefore, greater consistency between local amenities and the enhancement of their associated products and services seems necessary in order to foster regional development.